Role of Neuropsychological Factors in Post Head Injury Symptoms of Complicated Mild-moderate Traumatic Brain Injury patients - Jay Ranjan; Akanksha Chaurasiya; Nityanand Pandey; Hari Shanker Asthana (Ψυχολογία: το Περιοδικό της Ελληνικής Ψυχολογικής Εταιρείας, 2024)
raumatic brain injury (TBI) is a significant public health issue. The prevalence of post-head injury symptoms is well documented. However, only a few studies have examined its predictors, specifically the role of the neurocognitive and affective components in post-head injury symptoms. To examine the predictive role of neurocognitive and affective factors in post-head injury symptoms of complicated mild to moderate TBI patients. Thirty-nine patients with a GCS score of 9 to 15 and evidence of radiological intracranial abnormality were recruited for the study. All patients were assessed with neurocognitive measures such as the Stroop test for inhibitory control, the AIIMS memory scale for memory, and the Trail Making Test (TMT) for attention. The psychological distress of patients was assessed with the Hospital Anxiety Depression Scale (HADS), and post-head injury symptoms were assessed with the Rivermead Post Concussive Symptom Questionnaire (RPCSQ). Logistic regression analyses were conducted with predictors as neurocognitive measures and HADS scores and criterion variables as subjectively reported post-head injury symptoms on RPCSQ. Psychological distress and attention score significantly predict the presence of post-head injury cognitive symptoms in participants with complicated mild to moderate TBI (p<.05). In contrast, severity of injury significantly predicted the presence of post-head injury symptoms in physical/ somatic domain (p<.05). Furthermore, psychological distress and memory scores significantly predict presence of affective symptoms in participants with complicated mild-moderate TBI (p<.05). These findings suggest the need of addressing psychological distress along with neurocognitive impairment as a crucial component in neurorehabilitation for participants with complicated mild-moderate TBI.